Mechanism of endogenous myc gene down-regulation in E mu-N-myc tumors. - Ma, A (1991)
Transgenic mouse lines carrying the N-myc oncogene deregulated by the immunoglobulin heavy-chain enhancer spontaneously develop B-lymphoid tumors (R. Dildrop, A. Ma, K. Zimmerman, E. Hsu, A. Tesfaye, R. DePinho, and F. W. Alt, EMBO J. 8:1121-1128, 1989; H. Rosenbaum, E. Webb, J. M. Adams, S. Cory, and A. W. Harris, EMBO J. 8:749-755). Permanent cell lines derived from these tumors (E mu-N-myc cell lines) express extremely high levels of the N-myc transgene but little or no detectable endogenous N-myc or c-myc. We have employed nuclear run-on assays to show that down-regulation of endogenous N- and c-myc expression occurs at the transcriptional level. To determine whether the lack of endogenous myc gene transcription is a direct effect of high-level N-myc transgene expression, we have generated Abelson murine leukemia virus (A-MuLV)-transformed cell lines from prelymphomatous E mu-N-myc mice (A-MuLV/E mu-N-myc cell lines). Although these A-MuLV/E mu-N-myc lines express very high levels of the N-myc transgene, they continue to transcribe the endogenous c-myc gene. These findings demonstrate that high-level N-myc gene expression alone does not necessarily lead to down-regulation of endogenous myc gene expression and suggest that events associated with transformation by N-myc may be critical to this process.